Effects of Flat and Uphill Cycling on the Power-duration Relationship - Hovorka, Matthias; Leo, Peter; Simon, Dieter; Prinz, Bernhard; Nimmerichter, Alfred (International Journal of Sports Medicine, 2022)
The purpose of this study was to investigate the effects of flat and uphill cycling on critical power and the work available above critical power. Thirteen well-trained endurance athletes performed three prediction trials of 10-, 4- and 1-min in both flat (0.6%) and uphill (9.8%) cycling conditions on two separate days. Critical power and the work available above critical power were estimated using various mathematical models. The best individual fit was used for further statistical analyses. Paired t-tests and Bland-Altman plots with 95% limits of agreement were applied to compare power output and parameter estimates between cycling conditions. Power output during the 10- and 4-min prediction trial and power output at critical power were not significantly affected by test conditions (all at p>0.05), but the limits of agreement between flat and uphill cycling power output and critical power estimates are too large to consider both conditions as equivalent. However, power output during the 1-min prediction trial and the work available above critical power were significantly higher during uphill compared to flat cycling (p<0.05). The results of this investigation indicate that gradient affects cycling time-trial performance, power output at critical power, and the amount of work available above critical power.
Keywords: critical power; field test; terrain slope; time trial; anaerobic work capacity; endurance